Binary polar liquids structural and dynamic characterization using spectroscopic methods - Mehrotra, Suresh C.; Kumharkhane, Ashok; Chaudhari, Ajay (Elsevier, 2017)
Binary Polar Liquids: Structural and Dynamic Characterization Using Spectroscopic Methods provides liquid state physical chemists and physicists with practical theoretical models based on a wealth of robust data that describe the dielectric properties of dipolar materials in a systematic manner. In many applications, reference measurements using dielectric permittivity data are required. Over the past three decades, the author has compiled and analyzed permittivity research data and relaxation times for various polar liquids and their mixtures. The resulting structural data - as determined from various models - is critically evaluated, arming scientists with a complete characterization of the spectra of water-containing mixtures.--Provided by publisher.